Enhancing Human Resources Competency in Indonesia Tourism Villages - Novantini Samodra, Vegalyra; Zahari, Yudhi Kurniawan; Arviciena Sakti, Reza (ShariaBiz International Journal of Economics & Business, 2024)
This study explored enhancing human resources in Indonesian tourism villages by emphasizing competency development for resilience, competitiveness and sustainability. It developed the New Public Governance (NPG) model and analyzed the ideal scenario and gaps in effectively implementing the model for tourism village human resources. The NPG model was designed from critically analyzing global literature on the interaction between governance, sustainable development and tourism. The study was conducted in Senggigi tourism village involving local government, residents, businesses, visitors and communities. Methods used were literature review, observation and interviews. The results proposed the NPG model to address challenges through collaboration, stakeholder engagement, flexibility, risk management and performance measurement. The ideal scenario highlighted the role of government and stakeholder collaboration in sustainable tourism development. Gaps identified included limited resources, engagement and bureaucratic instability. Addressing these requires coordinated efforts to build capacity, improve structures and foster inclusive, sustainable tourism.